2017
DOI: 10.21767/2171-6625.1000174
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Effect of a 2-Hour Walk in Kumano-Kodo Forest

Abstract: Background: Studies have shown that walking in forests can have a relaxation effect, but the participants only walked for about 15 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Both Yamaguchi et al [19] and Hohashi & Kobayashi [44] claim that, although the SAA concentration did not have a significant change after visiting forests, the tendency toward a decline of SAA suggests its potential effects on relaxation. Positive effects of forest bathing on relaxation have been confirmed in other studies with different experimental designs [18]. Komori et al [18] compared participants' SAA in two different environmental settings.…”
Section: Response Of Saamentioning
confidence: 85%
See 3 more Smart Citations
“…Both Yamaguchi et al [19] and Hohashi & Kobayashi [44] claim that, although the SAA concentration did not have a significant change after visiting forests, the tendency toward a decline of SAA suggests its potential effects on relaxation. Positive effects of forest bathing on relaxation have been confirmed in other studies with different experimental designs [18]. Komori et al [18] compared participants' SAA in two different environmental settings.…”
Section: Response Of Saamentioning
confidence: 85%
“…Positive effects of forest bathing on relaxation have been confirmed in other studies with different experimental designs [18]. Komori et al [18] compared participants' SAA in two different environmental settings. They found that participants in a forest setting had a significant lower SAA than those in an urban setting, proving the function of forests in reducing stress.…”
Section: Response Of Saamentioning
confidence: 85%
See 2 more Smart Citations
“…Of course there are many limitations to this study and thus future directions for research indicated by these results. Others have found within-individual effects of walking in nature versus urban areas, with greater decreases in salivary cortisol following exposure to natural areas 16 , 17 indicating that self-selection for outdoor recreation is unlikely to be driving the observed effects. Urban dwellers prescribed a ‘nature pill’ also showed decreases in salivary cortisol following exposures to natural areas 18 .…”
Section: Discussionmentioning
confidence: 98%